Effect of pamelo orange (Citrus maxima) peel ethanol extract on burn healing in white rats (Rattus novergicus) - Sukmawati; Kamri, Andi Maulana; Eni, Nur Syahira Atika (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Burns are injuries resulting from tissue damage caused by contact with a heat source. The ethanol extract of pamelo orange peel (Citrus maxima) contains alkaloids, tannins, flavonoids, and saponins, which have been shown to enhance wound healing by accelerating epithelialization. This study aimed to evaluate the effect and determine the most effective concentration of ethanol extract of pamelo orange peel on burn wound healing in white rats. Sixteen rats were divided into four groups: a negative control group treated with 1% CMC-Na, two treatment groups receiving 3% and 6% ethanol extract of pamelo orange peel, and a positive control group treated with Lanakeloid-E®. Burns were induced on the rats' backs using a hot plate, followed by topical treatment for 21 days. Wound area measurements were taken on days 1, 4, 8, 12, 16, and 21 using a caliper. The results indicated that the ethanol extract of pamelo orange peel significantly promoted wound healing in the treated rats. Both the 3% and 6% concentrations reduced wound diameter, with the 3% concentration proving to be the most effective, achieving an 86.86% wound healing rate. The effectiveness of the extract is likely due to the presence of alkaloids, tannins, flavonoids, and saponins.